Interpolation of Microclimatic Parameters Over Capsicum Under Open Ventilated Greenhouse - Chauhan, K. K.; Lunagaria, M. M. (International Journal of Economic Plants, 2022)
A network of 12 grid points was recorded over capsicum crop to interpolate different weather parameters in the open ventilated greenhouse, an environment that differs markedly from open sites. The microclimatic condition was observed at 4.75-meter interval ground area in 4×3 regular grids. The series analyzed consisted of weekly observations recorded for a season. Most part under greenhouse had PAR distribution in range of 200−250 μ mol m-2 s-1. Regressions model were used to describe relations between photosynthetically active radiation, Relative Humidity, Air Temperature and Soil Temperature under open ventilated greenhouse to predict inside microclimatic condition. As the air temperature prevailed under greenhouse and open field condition was close during most observations, there was strong association (r=0.96**). Relative humidity also showed significant association (r=0.8**) and functional relationship with coefficient of determination R2=0.63. PAR and soil temperature also showed highly significant association with correlation coefficient r = 0.79** and r=0.9**, respectively.